THE REFUTATION TEXT IN POE TO REDUCE THE QUANTITY OF STUDENTSâ MISCONCEPTION - Muliyani, Riski (LPPM Undiksha, 2018)
The aim of this paper is to know the decreasing of the quantity studentâs misconceptions after given a Refutation Text in Predict-Observe-Explain (POE) learning model by researcher. The hydrostatic pressure misconceptions consist of four sub-misconceptions. This research is a quantitative research with weak experimental design. Sampling technique applied purposive sampling and has involve 32 students on 9th grade of junior high school in Pandeglang, Banten, Indonesia. The diagnostic test is a multiple-choice form with three-tier test (TTT) format. The result of this research founded that there are decreasing of the quantity of studentâs misconception on the hydrostatic pressure. The largest percentage decreasing of the quantity of studentâs misconception is on the misconceptions 1 about 79.31%. Misconceptions 1 is the magnitude of Hydrostatic Pressure inversely proportional to it area surface. For the future research, suggested to combine strategies or methods for optimal decreasing the quantity of studentâs misconceptions